Earning Management and Risk Profile in the Banking Industry: Case Study from Indonesia - Winoto Tj, Hery; ., . (International Journal of Engineering and Technology, 2018)
This study aims to investigate the application of earnings management and risk profile in the banking industry in Indonesia, during the period 2008-2017 data on 41 banks listed on the Stock Exchange. This research use analysis technique of FMOLS regression data by first doing correlation test by using correlogram. From the research that has been conducted in the results that there is a very significant relationship between earnings management and risk profile in 41 banks in Indonesia.Â Â